THE APPLICATION OF TALOGTIKA MEDIA TO IMPROVE MATHEMATICS LEARNING OUTCOMES AT SMK GENERASI MANDIRI - Alfahnum, Mal; Masitha Astriani, Maya (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
This study aims to determine whether the use of talogtika media can improve student learning outcomes in mathematics subjects on logarithms at SMK Generasi Mandiri. This study uses a quantitative approach with the Quasi Experimental Design method. The population in this study were all class X students at SMK Generasi, while the sample was class X TKJ 1 which consisted of 32 students. The results of the research and analysis showed that there was a significant increase in student learning outcomes after talogtika media was applied. The increase in scores reached 35 points. This can be seen from the pre-test results which had an average of 47.5 and a post-test of 82.5. The difference in scores between the pre-test and post-test was 35 points. The application of talogtika media in improving student learning outcomes in mathematics subjects for class X shows that this media can be an effective way to improve learning outcomes, because talogtika media helps students understand the material more easily during the learning process.